Clostridium difficile modulates host innate immunity via toxin-independent and dependent mechanism(s) - Jafari, Nazilla V.; Kuehne, Sarah A.; Bryant, Clare E.; Elawad, Mamoun; Wren, Brendan W.; Minton, Nigel P.; Allan, Elaine; Bajaj-Elliott, Mona (Public Library of Science, 2013)
Clostridium difficile infection (CDI) is the leading cause of hospital and community-acquired antibiotic-associated diarrhoea and currently represents a significant health burden. Although the role and contribution of C. difficile toxins to disease pathogenesis is being increasingly understood, at present other facets of C. difficile-host interactions, in particular, bacterial-driven effects on host immunity remain less studied. Using an ex-vivo model of infection, we report that the human gastrointestinal mucosa elicits a rapid and significant cytokine response to C. difficile. Marked increase in IFN-γ with modest increase in IL-22 and IL-17A was noted. Significant increase in IL-8 suggested potential for neutrophil influx while presence of IL-12, IL-23, IL-1β and IL-6 was indicative of a cytokine milieu that may modulate subsequent T cell immunity. Majority of C. difficile-driven effects on murine bone-marrow-derived dendritic cell (BMDC) activation were toxin-independent; the toxins were however responsible for BMDC inflammasome activation. In contrast, human monocyte-derived DCs (mDCs) released IL-1β even in the absence of toxins suggesting host-specific mediation. Infected DC-T cell crosstalk revealed the ability of R20291 and 630 WT strains to elicit a differential DC IL-12 family cytokine milieu which culminated in significantly greater Th1 immunity in response to R20291. Interestingly, both strains induced a similar Th17 response. Elicitation of mucosal IFN-γ/IL-17A and Th1/Th17 immunity to C. difficile indicates a central role for this dual cytokine axis in establishing antimicrobial immunity to CDI.